Icariin Ameliorate Thiram-Induced Tibial Dyschondroplasia via Regulation of WNT4 and VEGF Expression in Broiler Chickens - Zhang, Hui; Mehmood, Khalid; Li, Kun; Rehman, Mujeeb U.; Jiang, Xiong; Huang, Shucheng; Wang, Lei; Zhang, Lihong; Tong, Xiaole; Nabi, Fazul; Yao, Wangyuan; Iqbal, Muhammad K.; et al. (Frontiers in Pharmacology, 2018)
Tibal dyschondroplasia (TD) is main bone problem in fast growing poultry birds that effect proximal growth plate of tibia bone. TD is broadly defined as non-vascularized and non-mineralized, and enlarged GP with tibia bone deformation and lameness. Icariin (Epimedium sagittatum) is a traditional Chinese medicine, which is commonly practiced in the treatment of various bone diseases. Recently, many researcher reports about the beneficial effects of Icariin in relation to various types of bone conditions but no report is available about promoting effect of icariin against TD. Therefore, current study was conducted to explore the ameliorating effect of icariin in thiram induced TD chickens. A total 180 broiler chicks were equally distributed in three groups; Control, TD induced by thiram (50 mg/kg) and icariin group (treated with icariin @10 mg/kg). All groups were administered with normal standard diet ad libitum regularly until the end of experiment. The wingless type member 4 (WNT4) and vascular endothelial growth factor (VEGF) genes and proteins expression were analyzed by quantitative real-time polymerase chain reaction and western blot analysis respectively. Tibial bone parameters, physiological changes in serum, antioxidant enzymes and chicken growth performance were determined to assess advantage and protective effect of the medicine in broiler chicken. The expression of WNT4 was decreased while VEGF increased significantly (P < 0.05) in TD affected chicks. TD enhanced the growth plate, lameness and irregular chondrocytes, while reduced the liver function, antioxidant enzymes in liver and performance of chickens. Icariin treatment up-regulated WNT4 and down regulated VEGF gene and protein expressions significantly (P < 0.05), restored the growth plate width, increased growth performance, corrected liver functions and antioxidant enzymes levels in liver, and mitigated the lameness in broiler chickens. In conclusion, icariin administration recovered growth plate size, normalized performance and prevented lameness significantly. Therefore, icariin treatments are encouraged to reduce the incidence of TD in broiler chickens.